Mujer y modernización demográfica en Pamplona - Anaut Bravo, Sagrario (Huarte de San Juan. Geografía e Historia, 1998)
The demographic change produced in Pamplona within process of demographic transition experiencing in most of Spanish provinces and its capitals, is not conceived without cultural evolutions, in habits of hygiene, work and nourishment, without a new valuation of childhood, maternity and health. All these factors pushed to the progressive reduction of ordinary mortality, a moderate limitation of births and a restriction of marriage rate. Everytimes, women, as a mother and as a responsible wife for the family, had to assume additional tasks of responsibilities to the maternity. In fact, it could not be such an advance in Pamplona’s population without a very active women participation’s. Their influence will be direct about marriage rate and fecundity, while their influence about mortality will play a role more indirect through their new responsabilities in the family.